CARACTERIZAÇÃO FÍSICO-QUÍMICA DO LODO GERADO NUM SISTEMA ANAERÓBICO DE TRATAMENTO DE EFLUENTES DE ORIGEM RESIDENCIAL - Guedes, Vagner (2013)
To avoid pollution and damage to the environment, Effluents need of treatment. The appropriate target these effluents should be the (STP), which are responsible for the removal of contaminants. The wastewater treatment plants seek to apply the same natural principles, using the same organisms that proliferate in soil and water, improving processes and minimizing costs to get the highest possible efficiency and can use aerobic or anaerobic processes. There is worldwide increasing production of waste, among which stands out the sewage sludge, generated by the sheer volume and complexity of management, which typically involves several processing steps. Chemical study was made of the sludge from the sludge blanket reactor (UASB) during the period of one year, using as the main techniques Fluorescence X-ray Absorption Spectroscopy Atomic Emission Spectroscopy for Flame, UV-vis spectroscopy and metal extraction by Tessier method, the parameters analyzed were pH, cation exchange capacity, sum of bases, exchangeable acidity, potassium, phosphorus mineral, organic phosphorus, nitrogen and metals: barium, cadmium, lead, copper, chromium, iron , nickel, manganese, silver, and zinc. x